MERCK SHARP & DOHME CORPORATION v COMPTROLLER GENERAL OF PATENTS, DESIGNS AND TRADE MARKS. Issue 6 (15th October 2018) - ,
Abstract: H1 Supplementary protection certificates – Construction of art.3(b) of the SPC Regulation – No UK marketing authorisation at date of application – Whether "End of Procedure" communication of approval to be treated as equivalent to granted marketing authorisation – Whether lack of marketing authorisation an "irregularity" – Whether capable of correction under art.10(3) of the SPC Regulation – Appeal to Patents Court – Reference to Court of Justice